ADVERSITY QUOTIENT DAN KEPUASAN KERJA TENAGA MARKETING OTOMOTIF KOTA PALEMBANG DI ERA PANDEMI COVID-19 - Johan Gunady Ony (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This research was conduted with the aim of measuring the level of adversity quotient and its effect on job satisfaction of Palembang automotive marketers in the era of the Covid-19 pandemic. The population in this research is the automotive (car) marketers in Palembang. The research sample was determined using a non probability sampling technique, namely convenience sampling, as many as 75 repondents. The result showed that the automotive marketers in Palembang was dominated by the Campers with moderate adversity quotient level. This research also shows that adversity quotient has a positive and significant effect on job satisfaction of automotive marketers in Palembang during the Covid-19 pandemic.